Analysing critical success factors in small and medium enterprises banking. (20th January 2015) - Vyas, Vishal; Raitani, Sonika; Roy, Ankur; Jain, Priyanka
A few years ago, Indian banks have avoided serving small and medium enterprises (SMEs) as a deliberate strategy due to the risk associated with it. Eventually, despite the several challenges posed by the SME segment, Indian banks have discovered appetite for such high risk–high return arena. This research aims to contribute the critical factors for profitable SME banking in India. This was achieved by means of confirmatory factor analysis. Data was obtained by a questionnaire survey of 234 bank employees of public and private sector banks in Uttar Pradesh state. A total of 22 individual critical factors were examined in this study. Fast and responsive services are considered as the most critical success factor. The research suggests to bank managers that it is crucial to take a holistic view of these factors when developing appropriate strategies for SME banking and channelling resources towards more critical aspects of SME business management.